Viral dynamics in patients with monkeypox infection: a prospective cohort study in Spain. Issue 4 (April 2023) - Suñer, Clara; Ubals, Maria; Tarín-Vicente, Eloy José; Mendoza, Adrià; Alemany, Andrea; Hernández-Rodríguez, Águeda; Casañ, Cristina; Descalzo, Vicente; Ouchi, Dan; Marc, Aurélien; Rivero, Àngel; Coll, Pep; et al.
Summary: Background: Monkeypox DNA has been detected in skin lesions, saliva, oropharynx, urine, semen, and stool of patients infected during the 2022 clade IIb outbreak; however, the viral dynamics within these compartments remain unknown. We aimed to characterise the viral load kinetics over time in various parts of the body. Methods: This was an observational, prospective, multicentre study of outpatients diagnosed with monkeypox in two hospitals and two sexual health clinics in Spain between June 28, 2022, and Sept 22, 2022. Men and women aged over 18 years were eligible if they reported having symptom onset within the previous 10 days of presentation, and were ineligible if disease was severe enough to be admitted to hospital. Samples were collected from five body locations (skin lesions, oropharynx, rectum, semen or vagina, and a dried blood spot) at six time points up to 57 days after the screening visit. Samples were analysed by quantitative PCR and a subset by cell culture. The primary endpoint was time from symptom onset to viral DNA clearance. Findings: Overall, 1663 samples were collected from 77 study participants. 75 (97%) participants were men, the median age was 35·0 years (IQR 29·0–46·0), and 39 (51%) participants were living with HIV. The median time from symptom onset to viral clearance was 25 days (95% CI 23–28) in the skin lesions, 16 days (13–19) in the oropharynx, 16 days (13–23) in the rectum, 13 days in semen (9–18), and 1 day in blood (0–5). The time from symptom onset to viral clearance for 90% of cases was 41 days (95% CI 34–47) in skin lesions and 39 days (27–56) in semen. The median viral load in skin lesions was 7·3 log10 copies per mL (IQR 6·5–8·2) at baseline, compared with 4·6 log10 copies per mL (2·9–5·8) in oropharyngeal samples, 5·0 log10 copies per mL (2·9–7·5) in rectal samples, 3·5 log10 copies per mL (2·9–4·7) in semen samples, and 4·0 log10 copies per mL (4·0–4·0) in blood specimens. Replication-competent viruses were isolated in samples with high DNA levels (>6·5 log10 copies per mL). Interpretation: In immunocompetent patients with mild monkeypox disease, PCR data alone would suggest a contact isolation period of 3 to 6 weeks but, based on detection of replication-competent virus, this time could be reduced. Based on findings from this cohort of patients, semen testing and prolonged use of condoms after recovery from monkeypox might not be necessary. Funding: University Hospital Germans Trias i Pujol and the YoMeCorono. Translation: For the Spanish translation of the abstract see Supplementary Materials section.